Prospective study on health-related quality of life, oral mucositis and oral health on during treatment of head and neck cancer - Charlott Karlsson; Niklas Bohm; Jessica Skoogh Andersson; Caterina Finizia; Annica Almståhl (BMC, 2024)
Abstract Background Few studies have examined health related Quality of Life (HR-QoL) during the treatment of head and neck cancer (HNC) with even fewer focusing on the impact of oral mucositis (OM) on HR-QoL. Studies performed during treatment of HNC makes it possible to follow fluctuations in HR-QoL, OM and other treatment related side effects. The aim was to prospectively analyze HR-QoL, changes in clinical variables and the impact of OM on HR-QoL during HNC treatment. Materials and methods Patients were recruited before commencing curative cancer treatment and were given professional oral care weekly during oncologic treatment. HR-QoL was reported before, during (week 2, 4 and 6) and three months after treatment using the EORTC Quality of Life questionnaires C30 and H&N35 and the stimulated whole salivary secretion rate was determined at the same time-points. OM (erythema and ulceration) was registered using the Oral Mucositis Assessment Scale (OMAS), at baseline, weekly during treatment and post treatment. Differences in HR-QoL between different timepoints were analyzed. To analyze the impact of OM on HR-QoL the patients were categorized into two groups: no/mild OM (OMAS ulceration score 0-1) or severe OM (OMAS ulceration score ≥ 2) and HR-QoL was compared between the two OM groups at three timepoints during treatment. Results Fifty-seven patients (43 men, 14 women), with a mean age of 58 years were included. Patients reported progressively impaired HR-QoL, with peak issues noted at weeks 4 and 6, particularly in social eating, senses, appetite loss, sticky saliva, and decreasing salivary secretion rates were determined. Patients with severe OM reported worse HR-QoL compared to those with no/mild OM. Persistent problems 3 months post treatment were appetite loss, dry mouth, senses (smell and taste) and problems with social eating. Conclusion Patients experienced exacerbated symptoms and problems weeks 4 and 6 of oncological treatment, especially among those with severe OM, stressing the importance of clinically monitoring the patients to reduce and alleviate their symptoms. Persistent problems three months post treatment are likely associated with the reduced salivary secretion rate indicating that patients should be monitored also after completed oncological treatment.